2002
DOI: 10.1034/j.1399-3054.2002.1150304.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of photorespiratory mutants from Lotus japonicus deficient in glutamine synthetase

Abstract: A mutagenesis programme using ethyl methanesulphonate (EMS) was carried out on Lotus japonicus (Regel) Larsen cv. Gifu in order to isolate photorespiratory mutants in this model legume. These mutants were able to grow in a CO2-enriched atmosphere [0.7% (v/v) CO2] but showed stress symptoms when transferred to air. Among them, three mutants displayed low levels of glutamine synthetase (GS; EC 6.3.1.2) activity in leaves. The mutants accumulated ammonium in leaves upon transfer from 0.7% (v/v) CO2 to air. F1 pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
59
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 49 publications
(108 reference statements)
3
59
0
Order By: Relevance
“…Previous studies showed that photorespiratory mutants of L. japonicus that are deficient in plastidic GS 2 accumulated NH 4 + at least during the first 24 h after exposure to normal CO 2 atmosphere (Orea et al, 2002). We aimed now to study the time course process of NH 4 + accumulation and to address the effect of an impaired photorespiratory cycle on an extended time scale.…”
Section: Kinetics Of Nhmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies showed that photorespiratory mutants of L. japonicus that are deficient in plastidic GS 2 accumulated NH 4 + at least during the first 24 h after exposure to normal CO 2 atmosphere (Orea et al, 2002). We aimed now to study the time course process of NH 4 + accumulation and to address the effect of an impaired photorespiratory cycle on an extended time scale.…”
Section: Kinetics Of Nhmentioning
confidence: 99%
“…In our laboratory, the first photorespiratory mutants of legumes were isolated from the model legume Lotus japonicus (Orea et al, 2002;Márquez, 2005;Márquez et al, 2005). These mutants, deficient in plastidic GS 2 , were further characterized at the molecular level (Betti et al, 2006) as well as nodule function (García-Calderón et al, 2012).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In rice, OsGS1;2 is localized in the surface cells of roots and is important in the primary assimilation of ammonium ions that are taken up by the roots, with OsGS1;1 in the roots being unable to compensate for the functions of OsGS1;2 [40]. 4 + that were released during photorespiration were very high and that the re-assimilation of this ammonium in the plant leaves was crucial for the efficiency of nitrogen use [42,43]. In our study, BnGS2 was expressed abundantly in the leaves, particularly during the seedling emergence and fiber development stages.…”
Section: Discussionmentioning
confidence: 99%